Implementation of Restaurant Tax Management Policy at the Regional Financial and Revenue Management Agency of Medan City - Sri Rezeki; Rahmat Daim Harahap (Journal of Indonesian Management, 2022)
In implementing the taxes of restaurant management policy in the financial and regional income management agency of Medan City, the purpose of this research is to find out the behaviour of the regulated policy and whether in implementing the policy it has been fully implemented by the Medan City Regional Tax Retribution Management Agency. The object of this research comes from primary data and secondary data. This research shows that there are still some that have not been realized from the applicable policies. The lack of supervision over the collection of Regional Taxes, especially in the Hotel and Restaurant Tax section, impacts tax arrears, which are significant in 2020, reaching 18 billion Indonesia Rupiah.